The Cost-Effectiveness of Tenofovir Alafenamide for Chronic Hepatitis B Virus in Taiwan - Elise Chia-Hui Tan; Alon Yehoshua; Sushanth Jeyakumar; Pongo Peng; Amy Lin; Nathaniel J. Smith; Nandita Kachru (MDM Policy & Practice)
Background. Chronic hepatitis B (CHB) is a lifelong disease requiring long-term or indefinite therapy, resulting in substantial economic burden. Thus, careful consideration must be used in the selection of therapies. Aim. This analysis assessed the cost-effectiveness of tenofovir alafenamide (TAF) compared with tenofovir disoproxil fumarate (TDF) and entecavir (ETV) from the perspective of the Taiwan National Health Insurance Administration Healthcare payer for the management of CHB over a lifetime horizon. Methods. An individual patient simulation model assessed the impact of treatment on CHB infection for liver- and safety-related outcomes. Patients could achieve spontaneous or treatment-induced responses, experience a reactivation of the disease, develop long-term liver complications, or experience treatment-related renal or bone complications. Patient population profiles were based on clinical trial and real-world data. Data on clinical parameters (safety, mortality, resistance risk, and flare), health utilities, and costs were sourced from the published literature. Results. TAF was associated with fewer liver disease events and fewer cases of bone and renal complications per 100 person-years. TAF also had higher eAg and sAg seroconversion compared with TDF and ETV. As compared with both treatments, TAF was both more effective and more costly, resulting in incremental cost-effectiveness ratios of USD 3,348 and USD 3,940 per quality-adjusted life-year gained versus TDF and ETV, respectively. Conclusion. TAF leads to better health outcomes at acceptable incremental costs compared with the most commonly used therapies in the management of CHB, thus making it a cost-effective option for the treatment of CHB in Taiwan. Highlights The cost-effectiveness of tenofovir alafenamide (TAF) versus tenofovir disoproxil fumarate (TDF) and entecavir (ETV) was assessed in patients with chronic hepatitis B in Taiwan. TAF was associated with fewer liver disease events, fewer cases of bone and renal complications, and higher eAG and sAG seroconversion compared with TDF and ETV; TAF was found to be cost-effective compared with both treatments.